THE LIKERT SCALE: EXPLORING THE UNKNOWNS AND THEIR POTENTIAL TO MISLEAD THE WORLD - Alhassn, I.; Asiamah, N.; Opuni, F. F.; Alhassan, A. (UDS International Journal of Development, 2022)
The Likert scale is such an admired and pervasive data collection tool, that has gained great recognition, especially in the last two decades. However, both seasoned and early-career researchers sometimes use it thoughtlessly in their investigations, resulting in the production of misleading research findings. This paper presents a general discourse on Likert scales and is a response to the misunderstandings surrounding their use, especially in recent years. The paper is based on secondary data and advances knowledge on research instrumentation using the Likert scale. We discussed some of the problems that can arise from the inappropriate use of the scale as well as strategies for reducing its impact on research findings. Thus, we proposed some remedies for dealing with “noisy” data obtained from a poorly constructed and guilelessly applied Likert scale. Eventually, we proposed a unified Likert scale that resolves the conflicting functions of descriptive anchors and numerical labelling of the scale. Keywords: Attitude, Continuum, Data, Likert scale, Psychometric